Adverse outcome pathways induced by 3,4‑dimethylmethcathinone and 4‑methylmethcathinone in differentiated human SH‑SY5Y neuronal cells - Soares, Jorge (2021)
Cathinones (β-keto amphetamines), widely abused in recreational settings, have been shown similar or even worse toxicological profile than classical amphetamines. In the present study, the cytotoxicity of two β-keto amphetamines [3,4-dimethylmethcathinone (3,4-DMMC) and 4-methylmethcathinone (4-MMC)], was evaluated in differentiated dopaminergic SH-SY5Y cells in comparison to methamphetamine (METH). MTT reduction and NR uptake assays revealed that both cathinones and METH induced cytotoxicity in a concentration- and time-dependent manner. Pre-treatment with trolox (antioxidant) partially prevented the cytotoxicity induced by all tested drugs, while N-acetyl-l-cysteine (NAC; antioxidant and glutathione precursor) and GBR 12909 dopamine transporter inhibitor) partially prevented the cytotoxicity induced by cathinones, as evaluated by the MTT reduction assay. Unlike METH, cathinones induced oxidative stress evidenced by the increase on intracellular levels of reactive oxygen species (ROS), and also by the decrease of intracellular glutathione levels. Trolox prevented, partially but significantly, the ROS generation elicited by cathinones, while NAC inhibited it completely. All tested drugs induced mitochondrial dysfunction, since they led to mitochondrial membrane depolarization and to intracellular ATP depletion. Activation of caspase-3, indicative of apoptosis, was seen both for cathinones and METH, and confirmed by annexin V and propidium iodide positive staining. Autophagy was also activated by all drugs tested. Pre-incubation with bafilomycin A1, an inhibitor of the vacuolar H+- ATPase, only protected against the cytotoxicity induced by METH, which indicates dissimilar toxicological pathways for the tested drugs. In conclusion, the mitochondrial impairment and oxidative stress observed for the tested cathinones may be key factors for their neurotoxicity, but different outcome pathways seem to be involved in the adverse effects, when compared to METH.